Assessment of adaptive capacity of spring wheat lines under conditions of Forest-Steppe zone of Ukraine - О. А. Демидов; С. О. Хоменко; І. В. Федоренко; Р. М. Близнюк; Є. А. Кузьменко (Plant Varieties Studying and Protection)
Purpose. Selecting spring wheat lines with increased adaptive capacity. Methods. Field experiments, statistical evaluation. Results. Lines of spring soft wheat with better adaptive capacity were identified (‘Erythrospermum 13-39’, ‘Lutescens 11-16’, ‘Lutescens 05-24’, ‘Lutescens 10-36’) and spring durum wheat (‘Melanopus 10-02’ (biotype II), ‘Melanopus 10-02’, ‘Melanopus 10-03’, ‘Hordeiforme 12-12’). Spring soft wheat varieties ‘Zlata’, ‘Dubravka’, ‘Oksamyt Myronivskyi’, ‘Bozhena’ and spring durum wheat varieties ‘MIP Raiduzhna’, ‘Magdalena’ with increased adaptive capacity were passed for State variety testing. Conclusions. With regard to the analysis of parameters of yield capacity and its variability under the influence of changing environmental factors, soft and durum spring wheat lines with increased adaptive capacity were identified. The best spring wheat lines for general adaptive capacity were passed for State variety testing. Soft spring wheat variety ‘Zlata’ and durum spring wheat variety ‘MIP Raiduzhna’, in 2014, and such soft spring wheat varieties as ‘Dubravka’, ‘Oksamyt Myronivskyi’, ‘Bozhena’ and spring durum wheat variety ‘Magdalena’, in 2015, were passed for State variety testing.